Analysis of the Impact of Changes in Local Revenue Realization Due to Increased Awareness of Paying Taxes at The Surabaya City Revenue Agencyconcise - Hayati, Cindy Nur; Marseto, Marseto; Wijaya, Riko Setya (Unram Journal of Community Service, 2025)
This research deeply explores the relationship between public awareness in paying taxes and its impact on increasing local revenue realization, a crucial aspect in the sustainability of regional development. In this context, the research employs a descriptive qualitative approach, which allows for an in-depth understanding of the dynamics at play, with a focus on secondary data analysis of local revenue realization. The main findings of this study underline the existence of a significant positive correlation between the level of public awareness in paying taxes and the increase in local revenue realization. More specifically, this study highlights the effectiveness of the *door-to-door* strategy as a highly influential method in raising public awareness of their tax obligations. This approach allows direct interaction between tax officers and taxpayers, which has proven to be effective in increasing public understanding, compliance, and ultimately, contribution to local revenue. In addition, this study also identified other factors that influence people's awareness in paying taxes, such as level of education, understanding of the benefits of taxes, and trust in local government. The implications of this study suggest that a more personalized and educative approach, such as the door-to-door method, is crucial in raising tax awareness. Overall, this study provides valuable insights into the importance of public awareness in paying taxes for increasing local revenue realization. The findings of this study can be the basis for local governments in formulating more effective policies and strategies to increase public awareness and compliance in paying taxes, so that in the end it can support sustainable regional development.